دورة المنخفض الهندي الموسمي وشدته على طقس ومناخ العراق - عدنان عبد الرحمن, ميسره; ميخائيل طليا, أ.م.د . جول (Journal of College of Education, 2023)
The research tackled the impact of the role of the Indian seasonal depression cycle on the Iraqi weather and climate which played a part in rising temperatures whenever it would be sunny in the center of the depression over India. The research included various stations in Iraq such as ; Mosul, Kirkuk, Khanaqin, Baghdad, Rutba and Basra from 1980-2017. Four years have been selected according to the highest temperatures  within the abovementioned period and  analyzed. Then, temperatures have been divided into three categories. It has been  concluded that the seasonal Indian depression impact is magnified in June concerning the study area and Basra and Khanaqin stations recorded the highest rate of staying and recurrence for 2017; as (40) frequency and (95) day were recorded by Basra station and (48) frequency and (82) day by Khanaqin station for the same year. While  Mosul and Rutba stations recorded less days of staying and recurrence.      The latest years from 2010 to 2017 were marked by recording higher days of staying and recurrence than the other years. And the research revealed domination of air indentations patterns and cutoff highs  at the pressure level (500) millibars. Within the same context, the highest average of temperature for the first category was (°47,1) C, and  for the second category was  (°48,8) C , for the third category was  (°51,5) C. Further, The highest average of temperature was recorded in 2017. And in 1998 (El Nino) phenomenon has emerged. The results of other  climatic factors such as; atmospheric pressure, wind speed and relative humidity  appeared with few differences between  the stations in question and reduction in  wind speed and relative humidity.
Keywords: Seasonal depression, temperatures, air indentations, cutoff highs, El Nino phenomenon, relative humidity.